2022
DOI: 10.1177/10556656221091699
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Health-Related Experiences of Individuals With Microtia and Craniofacial Microsomia and Their Families: Narrative Review Over 2 Decades

Abstract: This paper describes 20 years of microtia and craniofacial microsomia (CFM) psychosocial and healthcare studies and suggests directions for clinical care and research. A narrative review of papers January 2000 to July 2021 related to psychosocial and healthcare experiences of individuals with microtia and CFM and their families. Studies (N = 64) were mainly cross-sectional (69%), included a range of standardized measures (64%), and were with European (31%), American (27%), or multinational (23%) samples. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“… 35 Studies on ACC, PPE and OIP reconstructions have all reported benefits of treatment on psychosocial outcomes and teasing. 12 , 36 Unfortunately, little research has been done on the psychosocial functioning of patients with microtia who have not undergone ear reconstruction. However, a previous prospective study reported a better psychosocial functioning in patients with microtia who had not opted for reconstruction compared to the preoperative groups of patients who had undergone reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Studies on ACC, PPE and OIP reconstructions have all reported benefits of treatment on psychosocial outcomes and teasing. 12 , 36 Unfortunately, little research has been done on the psychosocial functioning of patients with microtia who have not undergone ear reconstruction. However, a previous prospective study reported a better psychosocial functioning in patients with microtia who had not opted for reconstruction compared to the preoperative groups of patients who had undergone reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…1 Multiple studies have documented the significant psychosocial impact that occurs with microtia, and team-based models of care are beginning to incorporate psychological and social services to address this important aspect of patient care. 2,3 Surgical reconstruction of the auricle is a mainstay of treatment to address psychosocial impacts of the condition. 2,4 Reconstruction occurs in multiple stages and can be done through autologous costal cartilage (ACC) or porous polyethylene implants.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Surgical reconstruction of the auricle is a mainstay of treatment to address psychosocial impacts of the condition. 2,4 Reconstruction occurs in multiple stages and can be done through autologous costal cartilage (ACC) or porous polyethylene implants. 5 In many cases, the reconstructed auricle may include hair-bearing skin of the scalp, motivating the use of laser epilation following reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large portion of our self-identity is housed within facial features. Patients with facial differences as a result of cranio­maxillofacial (CMF) trauma, such as sports injuries and road accidents, congenital anomalies, infectious disease, tumor resection, or edentulism have reported associated stressors of self-acceptance, negative responses of others, and difficulty coping with associated impairments. These associated impairments can include compromised sensory organ function, speech, and mastication . The field of CMF surgery treats a diverse range of ages and pathologies, both of which must be considered when CMF surgeons form and execute their surgical plan.…”
Section: Introductionmentioning
confidence: 99%